Taxation of Retained Profits of Enterprises and Income from Capital Assets - Manfred Rose (Wirtschaftsdienst)
Abstract The reduced taxation of retained profits under German income tax law is only rarely used. It is in fact extremely complicated and, taking into account the tax on its later withdrawal, even leads to a higher burden than normal taxation. To reform this tax law, a taxation of profits adjusted for notional interest on equity is proposed. Re-tained portions can be taxed at a proportional rate of 25 %. If they are withdrawn later, they are subject to progressive income taxation with full offsetting of the proportional tax paid. In order to ensure equal tax treatment with parts of income from capital assets accumulated in a qualified bank account, these are to be taxed according to the same concept.